Identification of a presymptomatic and early disease signature for amyotrophic lateral sclerosis (ALS): protocol of the premodiALS study - Tzeplaeff, Laura; Galhoz, Ana; Meijs, Clara; Caldi Gomes, Lucas; Kovac, Andrej; Menzel, Amrei; Değirmenci, Hatice; Alaamel, Abir; Kaya, Hüseyin Can; Çelik, Ali Günalp; Dinçer, Sine; Korucuk, Meltem; et al. (Neurological research and practice, 2025)
Introduction The median time to diagnosis of amyotrophic lateral sclerosis (ALS) is approximately 12 months after the onset of first symptoms. This diagnostic delay is primarily due to the nonspecific nature of early symptoms and the clinical challenges in differentiating ALS from its mimics. Therefore, the discovery of reliable biomarkers for the early and accurate diagnosis of ALS represents a critical medical need. Methods A total of 330 participants will be recruited across six international study sites. The cohort will include (1) pre-symptomatic gene mutation carriers, (2) symptomatic individuals up to 12 months after symptom onset with either ALS, ALS mimics, or a pure motor syndrome with yet unclear assignment, and (3) healthy controls. Participants will engage in a one-year longitudinal study, consisting of an initial evaluation at baseline visit and a follow-up visit 12 months later. Assessments will include an environmental and medical history questionnaire, neurological examinations, olfactory testing, cognitive/behavioral evaluations, and the collection of biological samples (serum, plasma, urine, tear fluid, and cerebrospinal fluid). Proteomic, metabolomic, and lipidomic analyses will be performed using mass spectrometry and targeted immunoassays, with all samples processed under standardized protocols. The resulting multimodal dataset will be systematically integrated in an effort to uncover a presymptomatic and early ALS signature. Perspective The premodiALS study aim to identify a clinico-molecular signature characteristic of presymptomatic and early ALS. These findings may have relevance to early diagnosis and future clinical practice for ALS disease.